1955
DOI: 10.1037/h0048070
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent probability and the efficiency of psychometric signs, patterns, or cutting scores.

Abstract: Efficiency in detecting poor adjustment cases. The efficiency of the scale can be evaluated in several ways. From the data in Table 1 it can be seen that if the cutting line given by the authors were used at Fort Ord, the scale could not be used directly to "screen out misfits." If all those predicted by the scale to make a poor adjustment were screened out, the number of false positives would be extremely high. Among the 10,000 potential inductees, 2080

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
701
0
7

Year Published

1956
1956
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,202 publications
(719 citation statements)
references
References 14 publications
9
701
0
7
Order By: Relevance
“…In causal inference, there is some preliminary evidence for this phenomenon. For example, in medical reasoning, clinicians often exhibit the fallacy when judging the probability of a disease (the cause) based on a set of symptoms (the effects) (Meehl & Rosen, 1955;Hammerton, 1973;Liu, 1975;Eddy, 1982). Despite the evidence for the inverse fallacy in these studies, Krynski and Tenenbaum (2007) suggested that the phenomenon is limited, only occurring when both probabilities have roughly the same value.…”
mentioning
confidence: 99%
“…In causal inference, there is some preliminary evidence for this phenomenon. For example, in medical reasoning, clinicians often exhibit the fallacy when judging the probability of a disease (the cause) based on a set of symptoms (the effects) (Meehl & Rosen, 1955;Hammerton, 1973;Liu, 1975;Eddy, 1982). Despite the evidence for the inverse fallacy in these studies, Krynski and Tenenbaum (2007) suggested that the phenomenon is limited, only occurring when both probabilities have roughly the same value.…”
mentioning
confidence: 99%
“…As such, the range-frequency model might not be directly applicable. However, some features of the model, such as the tendency to use categories with equal frequencies, might explain the general tendency to ignore base rates (Balla, Elstein, & Gates, 1983;Casscells, Schoenberger, & Grayboys, 1978;Kahneman & Tversky, 1973;Meehl & Rosen, 1955). Furthermore, insofar as these three more specific axes tend to tap more global evaluative dimensions, similar contextual effects should be expected, and range-frequency theory would be directly applicable.…”
Section: Discussionmentioning
confidence: 99%
“…The classic paper analyzing these difficulties, by Meehl and Rosen, delineated two types of error: false negatives and false positives (Meehl and Rosen, 1955). Correctly discerning the condition in question, in those who actually have the condition, is called 'sensitivity'.…”
Section: Predicting Rare Events Validating Surrogate Markers Of Rare mentioning
confidence: 99%